Anode catalyst layer slurry and preparation method and application thereof
By adding hydrophilic silica particles to the anode catalytic layer slurry and using high-pressure homogeneous dispersion technology, the anode flooding problem is solved, the output power of the fuel cell is improved, and the structural integrity of the catalyst layer is maintained.
Patent Information
- Application Number
- CN202311252693.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-26
AI Technical Summary
The prior art does not work well when improving the anode flooding problem, or it may damage the anode catalyst layer structure and affect the performance of the fuel cell.
An anode catalytic layer slurry including hydrophilic silica particles, catalysts, ionomers and solvents is prepared by high-pressure homogeneous dispersion technology to control the contact angle and particle size of the hydrophilic silica particles to improve the water distribution and drainage capacity of the anode catalytic layer.
It effectively improves the anode flooding effect, improves the output power of the fuel cell, and does not destroy the anode catalyst layer structure, ensuring the stability of the fuel cell performance.
Smart Images

Figure BDA0004470785890000071
Abstract
Description
Technical Field
[0001] The present invention relates to the field of fuel cells, and in particular to an anode catalyst layer slurry and a preparation method and application thereof. Background Art
[0002] The membrane electrode assembly (MEA) is the core unit of the proton exchange membrane fuel cell, and the anode and cathode catalyst layers are the core parts of the MEA. The catalyst layer is not only the place for electrochemical reactions, but also provides a transport channel for protons, electrons, reaction gases and water. Its structure plays a decisive role in the performance and life of the MEA.
[0003] At present, the proton exchange membrane (PEM) fuel cells used in vehicles will experience anode flooding after long-term operation, which further hinders the transportation of hydrogen on the anode side, resulting in insufficient hydrogen supply to the battery, causing a significant drop in the performance of the fuel cell and a serious lack of output power, affecting the user experience.
[0004] In order to improve the anode flooding problem, existing technologies often use system control strategies or improved anode side flow field design. System control strategies, such as cell voltage and exhaust gas monitoring and flushing the anode side, can eliminate nitrogen or water accumulated in the battery, but will cause irreversible damage to the structure of the anode catalyst layer, thereby affecting the performance of the fuel cell. Improved anode flow field design can improve the drainage capacity of the anode side to a certain extent, but the improvement effect is often poor and cannot fundamentally solve the problem of anode flooding.
[0005] Therefore, it is necessary for the present invention to provide a new anode catalyst layer slurry and a preparation method thereof to solve the problems in the prior art of improving anode flooding, such as poor effect of improving anode flooding or damage to the anode catalyst layer structure. Summary of the invention
[0006] The main purpose of the present invention is to provide an anode catalyst slurry and a preparation method and application thereof, so as to solve the problems in the prior art of improving anode flooding, such as poor improvement of anode flooding or destruction of the anode catalyst layer structure.
[0007] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, an anode catalyst layer slurry is provided, which includes hydrophilic silica particles, a catalyst, an ionomer and a solvent; the powder contact angle of the hydrophilic silica with water is 10° to 70°, and the particle size of the hydrophilic silica particles is 5 to 50 nm.
[0008] Furthermore, the anode catalyst layer slurry includes, by weight percentage, 1 to 20 wt % of hydrophilic silica particles, 1 to 20 wt % of a catalyst, 2 to 20 wt % of an ionomer, and 40 to 80 wt % of a solvent.
[0009] Furthermore, the anode catalyst layer slurry includes 2-10 wt% of hydrophilic silica particles, 5-15 wt% of catalyst, 2-15 wt% of ionomer and 60-80 wt% of solvent.
[0010] Furthermore, the specific surface area of the hydrophilic silica particles is 200 to 450 m 2 / g, the purity of the hydrophilic silica particles is greater than 99.9%.
[0011] Furthermore, the catalyst contains a Pt element, and preferably the catalyst is selected from one or more of Pt, Pt-alloy or Pt / C.
[0012] Further, the ionomer is selected from perfluorosulfonic acid resin.
[0013] Furthermore, the solvent is selected from water and / or alcohol solvents.
[0014] Furthermore, the alcohol solvent is selected from one or more of methanol, ethanol, ethylene glycol, n-propanol, isopropanol or glycerol.
[0015] Furthermore, in the catalyst, the content of Pt element is 20-100 wt%.
[0016] According to one aspect of the present invention, a method for preparing an anode catalyst layer slurry is provided, which comprises: mixing hydrophilic silica particles, a catalyst, an ionomer and a solvent and performing high pressure homogenization dispersion to obtain an anode catalyst layer slurry.
[0017] Furthermore, the pressure of the high-pressure homogenization dispersion is 100-150 MPa.
[0018] Furthermore, the high pressure homogenization dispersion is performed 2 to 5 times.
[0019] Furthermore, before the high-pressure homogenization dispersion, the preparation method further comprises the step of stirring the mixture of the hydrophilic silica particles, the catalyst, the ionomer and the solvent.
[0020] Furthermore, the stirring speed is 500-800 rpm, and the stirring time is 1-12 h.
[0021] Furthermore, the preparation method also includes first mixing the catalyst with the first part of the solvent, then adding the hydrophilic silica particles to the system, continuing to add the second part of the solvent to the system for stirring, and adding the ionomer during the stirring process.
[0022] According to another aspect of the present invention, there is also provided an anode catalyst layer for a proton exchange membrane, which is obtained by coating and transferring the aforementioned anode catalyst layer slurry.
[0023] The technical solution of the present invention is applied. The present invention adds silica particles to the anode catalyst layer slurry, which are hydrophilic and have a powder contact angle of 10° to 70° with water. When the powder contact angle of the hydrophilic silica particles with water is too high, the anode catalyst layer will have insufficient ability to bind water, and the uniform distribution of water under high electric density cannot be improved, resulting in local water blockage in the flow channel, which seriously affects the performance of the membrane electrode; when the powder contact angle of the hydrophilic silica particles with water is too low, the catalyst layer will bind a large amount of liquid water, resulting in the inability to remove water and the inability of the reaction gas to be transported to the catalyst surface, which seriously affects the performance of the membrane electrode. When the powder contact angle of the hydrophilic silica with water is 10° to 70°, a thin layer of water can be adsorbed on the surface of the anode catalyst layer, which can greatly improve the water distribution of the anode catalyst layer, is not easy to block the gas flow channel, is conducive to drainage, and can further improve the battery performance (high-density batteries can also be used), such as increasing the output power. At the same time, the hydrophilic silica particles of the present invention have a particle size of 5 to 50 nm, and have excellent dispersibility in the anode catalyst layer slurry, making the material performance uniformity better. Moreover, the introduction of hydrophilic silica particles into the anode catalyst layer will neither have a negative impact on the electrical performance of the battery nor destroy the anode catalyst layer structure, thereby not affecting the performance of the fuel cell. DETAILED DESCRIPTION
[0024] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0025] As described in the background technology section of this application, in the prior art, when improving anode flooding, there are problems such as poor improvement of anode flooding or destruction of the anode catalyst layer structure. In order to solve this problem, this application provides an anode catalyst layer slurry, which includes hydrophilic silica particles, a catalyst, an ionomer and a solvent; the hydrophilic silica particles have a powder contact angle with water of 10° to 70°, and the particle size of the hydrophilic silica particles is 5 to 50 nm.
[0026] The present invention adds silica particles to the anode catalyst layer slurry, which is hydrophilic and has a powder contact angle of 10° to 70° with water. When the powder contact angle of the hydrophilic silica particles with water is too high, the anode catalyst layer will have insufficient ability to bind water, and will not be able to improve the uniform distribution of water under high current density, resulting in local water blockage in the flow channel, which seriously affects the performance of the membrane electrode; when the powder contact angle of the hydrophilic silica particles with water is too low, the catalyst layer will bind a large amount of liquid water, resulting in the inability to remove water and the inability of the reaction gas to be transported to the catalyst surface, which seriously affects the performance of the membrane electrode. The applicant found that when the powder contact angle of the hydrophilic silica with water is 10° to 70°, a thin layer of water can be adsorbed on the surface of the anode catalyst layer, which can greatly improve the water distribution of the anode catalyst layer, is not easy to block the gas flow channel, is conducive to drainage, and can further improve the battery performance (high-density batteries can also be used), such as increasing the output power. At the same time, the hydrophilic silica particles of the present invention have a particle size of 5 to 50 nm, and have excellent dispersibility in the anode catalyst layer slurry, making the material performance uniformity better. Moreover, the introduction of hydrophilic silica particles into the anode catalyst layer will neither have a negative impact on the electrical performance of the battery nor destroy the anode catalyst layer structure, thereby not affecting the performance of the fuel cell.
[0027] In summary, the hydrophilic silica particles with the above properties have good compatibility with other components of the anode catalyst layer slurry, and can prepare a uniform anode catalyst layer. The components in the anode catalyst layer work together to fully exert the performance of the anode catalyst layer. It has excellent water management capabilities. The water generated by the battery during the catalytic reaction is not easy to accumulate on the surface of the anode catalyst layer, and hydrogen is easy to transfer, which effectively improves the anode flooding effect and will not destroy the structure of the anode catalyst layer, thereby not affecting the performance of the fuel cell.
[0028] In order to further improve the anode flooding effect, the powder contact angle between the hydrophilic silica particles and water is 30° to 60°, and the particle size of the hydrophilic silica particles is 5 to 15 nm.
[0029] In a preferred embodiment, the anode catalyst layer slurry includes 1-20wt% of hydrophilic silica particles, 1-20wt% of catalyst, 2-20wt% of ionomer and 40-80wt% of solvent by weight percentage. When the present invention controls the components of the anode catalyst layer slurry in the above proportions, the anode catalyst layer slurry can obtain a suitable solid content (5-20wt%), which is conducive to the subsequent coating to obtain a uniform, stable, and comprehensive performance anode catalyst layer, so that the anode catalyst layer has better water management capabilities, and further improves the anode flooding problem of the anode catalyst layer. The anode catalyst layer has a stronger drainage capacity and a faster gas mass transfer rate, which is conducive to the subsequent application in the battery with better output power.
[0030] The present invention controls the weight of the hydrophilic silica particles in the anode catalyst layer slurry to 1-20wt% based on the following considerations: when the weight of the hydrophilic silica particles in the anode catalyst layer slurry is too high, the body resistance and contact resistance of the anode side will increase, resulting in a decrease in the membrane electrical output power; when the weight of the hydrophilic silica particles in the anode catalyst layer slurry is too low, the ability of the anode coating to bind water will be weakened, and the liquid water on the anode side cannot be evenly distributed, affecting the hydrogen transmission efficiency.
[0031] In order to further improve the anode flooding effect, the anode catalyst layer slurry includes 2-10 wt% of hydrophilic silica particles, 5-15 wt% of catalyst, 2-15 wt% of ionomer and 60-80 wt% of solvent.
[0032] In order to further improve the anode flooding effect, the specific surface area of the hydrophilic silica particles is 200-450m 2 / g (for example, preferably 200m 2 / g, 220m 2 / g, 250m 2 / g, 280m 2 / g、300m 2 / g, 320m 2 / g, 350m 2 / g, 350m 2 / g、380m 2 / g, 400m 2 / g, 420m 2 / g and 450m 2 / g), and the purity of the hydrophilic silica particles is greater than 99.9%.
[0033] The present invention limits the specific surface area of the hydrophilic silica particles to 200-450 m 2 / g, hydrophilic silica particles can promote the adsorption of a thin layer of water on the surface of the anode catalyst layer. If the specific surface area is too high, exceeding 450m 2 / g, it is easy to cause the catalyst layer to combine with a large amount of liquid water, resulting in the inability to remove water and the inability of the reaction gas to be transported to the catalyst surface, which seriously affects the performance of the membrane electrode. If the specific surface area is less than 200m 2 / g, the anode catalyst layer has a low ability to bind water, and cannot improve the uniform distribution of water under high current density, resulting in local flooding and affecting the performance of the membrane electrode. By limiting the specific surface area of the hydrophilic silica particles to the above range, the hydrophilic silica particles can further improve the water distribution of the anode catalyst layer, are not easy to block the gas flow channel, are conducive to drainage, and can further improve the battery performance.
[0034] In order to further improve the catalytic efficiency of the anode catalyst layer, the catalyst contains Pt element. Preferably, the catalyst is selected from one or more of Pt, Pt-alloy or Pt / C. More preferably, the content of Pt element in the catalyst is 20-100wt%.
[0035] In an optional embodiment, the ionomer may be selected from perfluorosulfonic acid resin, but is not limited to the above ionomer types, and other conventional ionomers in the art may also be selected.
[0036] In order to further improve the stability and uniformity of the anode catalyst layer slurry, the solvent is selected from water and / or alcohol solvents, and preferably the alcohol solvent is selected from one or more of methanol, ethanol, ethylene glycol, n-propanol, isopropanol or glycerol.
[0037] Another aspect of the present invention provides a method for preparing an anode catalyst layer slurry, wherein hydrophilic silica particles, a catalyst, an ionomer and a solvent are mixed and homogenized and dispersed under high pressure to obtain an anode catalyst layer slurry.
[0038] The present invention mixes hydrophilic silica particles, catalyst, ionomer and solvent, and then performs high-pressure homogenization dispersion. The present invention adopts high-pressure homogenization dispersion to make the slurry form a supersonic fluid in the dispersion chamber, and the catalyst cluster particles in the slurry are broken after collision and cavitation, and the particle size becomes smaller, and the micron-scale catalyst cluster body is dispersed and processed into nano-scale cluster particles. The smaller the catalyst particles, the more stable the slurry system tends to be, the more uniform the distribution of components in the system, and the obtained anode catalyst layer is smoother and has no defects. The performance of the anode catalyst layer obtained by the above-mentioned preparation method can be fully utilized, so that it has a better water management ability, is conducive to drainage and gas mass transfer, and effectively solves the problem of anode flooding.
[0039] In order to obtain a more stable and uniform anode catalyst layer slurry, the ionomer is added in the form of an ionomer solution, and preferably the weight fraction of the ionomer in the ionomer solution is 2 to 40 wt %.
[0040] In order to obtain a more stable and uniform anode catalyst layer slurry, in some optional embodiments, the pressure of the high-pressure homogenization dispersion is preferably 100-150Mpa (for example, preferably 100Mpa, 120Mpa, 140Mpa, 150Mpa); preferably, the number of high-pressure homogenization dispersion is 2-5 times; the method for preparing the catalyst layer slurry also includes the step of first stirring the mixture of hydrophilic silica particles, catalyst, ionomer and solvent; preferably, the stirring speed is 500-800rpm (for example, preferably 500rpm, 550rpm, 600rpm, 650rpm, 700rpm, 750rpm, 800rpm), and the stirring time is 1-12h.
[0041] In a preferred embodiment, the method for preparing the anode catalyst layer slurry further comprises first mixing the catalyst with a first portion of the solvent, then adding hydrophilic silica particles to the system, continuing to add a second portion of the solvent to the system for stirring, and adding an ionomer during the stirring process.
[0042] In order to further improve the uniformity and stability of the anode catalyst layer slurry, the present invention divides the solvent into two parts and adds them twice. First, the catalyst is mixed with part of the solvent and then the hydrophilic silica particles are added, so that the solid particles are first dispersed in the solvent, and then another part of the solvent is added to the slurry system for stirring. While stirring, the ionomer is added. This part of the solvent can be beneficial to the dispersion of the solid particles in the ionomer, and avoid the high viscosity of the ionomer causing the solid particles to agglomerate. The anode catalyst layer slurry is added in the above order, so that the solid particles of the anode catalyst layer slurry can be more dispersed, not easy to agglomerate, and the coating effect is better when the anode catalyst layer is prepared later, and the obtained anode catalyst layer is smoother and more defect-free.
[0043] In an optional embodiment, when the solvent is selected from water and alcohol solvents, the catalyst and water are first mixed evenly, and then the hydrophilic silica particles are added. Then, the alcohol solvent is added to the system and stirred and mixed, and the ionomer is added while stirring.
[0044] Another aspect of the present invention provides an anode catalyst layer for a proton exchange membrane, which is obtained by coating and transferring the anode catalyst layer slurry of the present invention.
[0045] Based on the reasons mentioned above, the anode catalyst layer for proton exchange membrane prepared by the present invention has excellent water management capabilities. The water generated by the battery during the catalytic reaction is not easy to accumulate on the surface of the anode catalyst layer, and hydrogen is easy to transfer, which effectively improves the anode flooding effect and will not destroy the structure of the anode catalyst layer, thereby not affecting the performance of the fuel cell.
[0046] In an optional embodiment, the method for preparing an anode catalyst layer for a proton exchange membrane includes: coating an anode catalyst layer slurry on one surface of a base membrane, drying to obtain a transfer membrane, and transferring the anode catalyst layer of the transfer membrane to one side of the proton exchange membrane by a thermal transfer process to form an anode catalyst layer for a proton exchange membrane on one side of the proton exchange membrane.
[0047] In order to better solidify the anode catalyst layer for the proton exchange membrane, preferably, the drying temperature is 60 to 80° C. and the drying time is 2 to 10 minutes.
[0048] In order to improve the transfer efficiency of the anode catalyst layer of the transfer film, preferably, the transfer temperature is 130-180° C., the transfer pressure is 6-10 kgf, and the hot pressing time during the transfer process is 1-3 min.
[0049] In order to further improve the performance of membrane electrode, the Pt loading of the anode catalyst layer of the proton exchange membrane is 0.05-0.1 mg / cm 2 The loading of hydrophilic silica particles in the anode catalyst layer is 0.01-0.1 mg / cm 2 .
[0050] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0051] Example 1
[0052] The anode catalyst layer slurry is composed of 3wt% hydrophilic silica particles (powder contact angle with water is 50°, particle size is 9nm, specific surface area is 380m 2 / g, purity is 99.9%), 8wt% Pt / C (the content of Pt element is 50wt%), 30wt% water, 43wt% n-propanol and 16wt% perfluorosulfonic acid resin solution (the content of perfluorosulfonic acid resin is 20wt%).
[0053] Preparation method of anode catalyst layer slurry: prepare hydrophilic silica particles, Pt / C, water, n-propanol and perfluorosulfonic acid resin solution according to the above-mentioned formula of anode catalyst layer slurry; first mix Pt / C with water, further add hydrophilic silica particles, and then add n-propanol for stirring, and add perfluorosulfonic acid resin solution during stirring, wherein the stirring speed is 700rpm, and the stirring time is 2h; after stirring and mixing, the mixture is subjected to high-pressure homogenization dispersion 3 times (pressure is 120MPa) to obtain anode catalyst layer slurry.
[0054] Example 2
[0055] The difference from Example 1 is that the anode catalyst layer slurry is composed of 20wt% hydrophilic silica particles (powder contact angle with water is 50°, particle size is 9nm, specific surface area is 380m 2 / g, purity is 99.9%. ), 8wt% Pt / C (the content of Pt element is 50wt%), 20wt% water, 40wt% n-propanol and 12wt% perfluorosulfonic acid resin solution (the content of perfluorosulfonic acid resin is 20wt%).
[0056] Example 3
[0057] The difference from Example 1 is that the anode catalyst layer slurry is composed of 10wt% hydrophilic silica particles (with a powder contact angle of 50° with water, a particle size of 9nm, and a specific surface area of 380m 2 / g, purity is 99.9%. ), 8wt% Pt / C (the content of Pt element is 50wt%), 30wt% water, 40wt% n-propanol and 12wt% perfluorosulfonic acid resin solution (the content of perfluorosulfonic acid resin is 20wt%).
[0058] Example 4
[0059] The difference from Example 1 is that the powder contact angle between the hydrophilic silica particles and water is 10°.
[0060] Example 5
[0061] The difference from Example 1 is that the powder contact angle between the hydrophilic silica particles and water is 70°.
[0062] Example 6
[0063] The difference from Example 1 is that the particle size of the hydrophilic silica particles is 50 nm.
[0064] Example 7
[0065] The difference from Example 1 is that the particle size of the hydrophilic silica particles is 5 nm.
[0066] Example 8
[0067] The difference from Example 1 is that the method for preparing the anode catalyst layer slurry does not include high-pressure homogenization and dispersion treatment.
[0068] Comparative Example 1
[0069] The only difference from Embodiment 1 is that the anode catalyst layer slurry does not include hydrophilic silica particles.
[0070] The anode catalyst layer slurry of this comparative example is composed of 8wt% of Pt / C catalyst (the content of Pt element is 50wt%), 33wt% of water, 43wt% of n-propanol and 16wt% of perfluorosulfonic acid resin solution (the content of perfluorosulfonic acid resin is 20%). The anode catalyst layer slurry is prepared by the same preparation method of the anode catalyst layer slurry as in Example 1.
[0071] Performance Testing
[0072] Preparation of fuel cell membrane electrode: The anode catalyst layer slurry and cathode catalyst layer slurry of the above-mentioned embodiment and comparative example are coated on the surface of the first substrate membrane and the second substrate membrane respectively, and dried at 70°C for 5 minutes to obtain a transfer film containing an anode catalyst layer and a transfer film containing a cathode catalyst layer. The anode catalyst layer and the cathode catalyst layer are transferred to both sides of the proton exchange membrane respectively by thermal transfer technology (transfer temperature is 150°C, transfer pressure is 8kgf, and hot pressing time is 1min), and then frame packaging is performed (packaging temperature is 160°C, pressure is 12kgf, and hot pressing time is 1min) to obtain a fuel cell membrane electrode.
[0073] The cathode catalyst layer slurry consists of 8wt% Pt / C (the content of Pt element is 50wt%), 30wt% water, 42wt% n-propanol and 20wt% perfluorosulfonic acid resin solution (the content of perfluorosulfonic acid resin is 20%).
[0074] The membrane electrode prepared in the above embodiment and comparative example was subjected to a single cell polarization test: hydrogen was passed through the anode at a stoichiometric ratio of 1.5, and air was passed through the cathode at a stoichiometric ratio of 1.5; the operating temperature was 70°C; the humidity of the anode and cathode was 40%, and the back pressure of the cathode and cathode was 250 kPa. The test results are shown in Table 1.
[0075] Table 1
[0076]
[0077] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An anode catalyst layer slurry, characterized in that: The anode catalyst layer slurry comprises hydrophilic silica particles, a catalyst, an ionomer and a solvent; the powder contact angle between the hydrophilic silica and water is 10° to 70°, and the particle size of the hydrophilic silica particles is 5 to 50 nm.
2. The anode catalyst layer slurry according to claim 1, characterized in that: In terms of weight percentage, the anode catalyst layer slurry comprises 1 to 20 wt % of the hydrophilic silica particles, 1 to 20 wt % of the catalyst, 2 to 20 wt % of the ionomer and 40 to 80 wt % of the solvent; Preferably, the anode catalyst layer slurry comprises 2-10 wt% of the hydrophilic silica particles, 5-15 wt% of the catalyst, 2-15 wt% of the ionomer and 60-80 wt% of the solvent.
3. The anode catalyst layer slurry according to claim 1 or 2, characterized in that: The specific surface area of the hydrophilic silica particles is 200 to 450 m 2 / g, and the purity of the hydrophilic silica particles is greater than 99.9%.
4. The anode catalyst layer slurry according to any one of claims 1 to 3, characterized in that: The catalyst contains a Pt element, and preferably the catalyst is selected from one or more of Pt, Pt-alloy or Pt / C; Preferably, the ionomer is selected from perfluorosulfonic acid resin; Preferably, the solvent is selected from water and / or alcohol solvents; Further preferably, the alcohol solvent is selected from one or more of methanol, ethanol, ethylene glycol, n-propanol, isopropanol or glycerol.
5. The anode catalyst layer slurry according to claim 4, characterized in that: In the catalyst, the content of Pt element is 20-100wt%.
6. A method for preparing an anode catalyst layer slurry according to any one of claims 1 to 5, characterized in that: include: The hydrophilic silica particles, catalyst, ionomer and solvent are mixed and homogenized under high pressure to obtain the anode catalyst layer slurry.
7. The method for preparing the anode catalyst layer slurry according to claim 6, characterized in that: The pressure of the high-pressure homogenization dispersion is 100-150 MPa; Preferably, the high-pressure homogenization dispersion is performed 2 to 5 times.
8. The method for preparing the anode catalyst layer slurry according to claim 7, characterized in that: Prior to the high-pressure homogenization dispersion, the preparation method further comprises the step of stirring a mixture of the hydrophilic silica particles, the catalyst, the ionomer and the solvent; Preferably, the stirring speed is 500-800 rpm, and the stirring time is 1-12 h.
9. The method for preparing the anode catalyst layer slurry according to claim 8, characterized in that: The preparation method further comprises first mixing the catalyst with the first part of the solvent, then adding the hydrophilic silica particles to the system, continuing to add the second part of the solvent to the system for stirring, and adding the ionomer during the stirring process.
10. An anode catalyst layer for a proton exchange membrane, characterized in that: The anode catalyst layer is obtained by coating and transferring the anode catalyst layer slurry according to any one of claims 1 to 5.
Citation Information
Patent Citations
Hydrophilic / hydrophobic compound multilayer membrane electrode and preparation method thereof
CN106229533A
Preparation method of hydrophobic high-elastic transparent spherical SiO2 aerogel
CN114408933A
Water-repellent type gas diffusion electrode, its formation method, and membrane-electrode assembly
JP2010040464A
Membrane electrode assembly for pemfc, method for preparing the same, and fuel cell using the same
KR100645832B1
Electrode structure for solid polymer type fuel cell
US20060068269A1